How Social Media Influencers Shape Consumer Perceptions and Buying Behavior at Inland Resorts: A Mixed-Methods Inquiry - Christine Mae G. Montenegro; Nenette D. Padilla (Philippine Social Science Journal)
As influencer marketing evolves, understanding its impact on specific industries becomes crucial. This mixed-methods study examines the influence of social media influencers (SMIs) on consumer perceptions and buying behaviors within the context of inland resorts. Using surveys and interviews with resort guests, the research measures the perceived impact of SMI characteristics on consumer decisions. Quantitative data is analyzed through mean and standard deviation, while qualitative data is explored using Lichtman's 3Cs thematic analysis. Findings indicate a strong influence of SMIs on consumer perception and purchasing behavior, with identified themes providing valuable insights for developing effective marketing strategies. This study highlights the need for further research on the role of SMIs in the broader hospitality and tourism sector.